Without Crossing a Border: Exploring the Impact of Shifting Study Abroad Online on Students’ Learning and Intercultural Competence Development during the COVID-19 Pandemic - Liu, Yingjie; Shirley, Thomas (Online learning (Newburyport, Mass.), 2021)
While all higher education was affected by the COVID-19 pandemic, study abroad programs were uniquely challenged by the associated restrictions and limitations. This case study integrates a Collaborative Online International Learning (COIL) pedagogy approach and virtual reality (VR) technologies into the curriculum redesign process to transform a business study abroad course into an online format. Using VR technology, U.S. students and their international partners in Germany, Brazil, and India created and shared cultural exchange virtual tours. The redesigned online study abroad course engaged students in active learning activities and cultivated students’ intercultural competence development.